ANALISIS DETERMINASI KEANDALAN DAN TIMELINESS PELAPORAN KEUANGAN - Nur Laila Yuliani; Barkah Susanto; Farida Farida (JAFFA, 2016)
This study is aimed at examining factors affecting the reliability and timeliness of financial reporting. These factors include human resources, utilization of information technology, internal control of accounting, organizational commitment and supporting system. The main ground of this study is an empirical study on the factors that affect the reliability and timeliness of financial reporting which have been varied in the results and increasingly important and strong public demands for accountability. The sample of this study consists of 83 employees in BLUDs around Kedu residency. The analysis of the data are measured through Partial Least Square (WarpPLS). This study provides an evidence that human resources, internal control of accounting, organizational commitment and supporting system have positive effects on the reliability of financial reporting. On the other hand, the utilization of information technology does not positively effect the reliability of financial reporting. Meanwhile, the utilization of information technology, internal control of accounting, and organizational commitment positively affects timeliness of financial reporting, while the human resources, and supporting system do no have positive effect on the timeliness of financial reporting.